2017
DOI: 10.1177/1350650117739159
|View full text |Cite
|
Sign up to set email alerts
|

Antiwear and extreme pressure performance of castor oil with nano-additives

Abstract: The aim of the present study is to examine the antiwear, antifriction, and extreme pressure performance of castor oil with nano-additives by using a four-ball tester. CeO2 (≈90 nm) and polytetrafluroethylene (≈150 nm) nanoparticles were used as an additive in castor oil with four different concentrations in the range of 0.1–1.0% w/v. The suspension stability of the nanoparticles was improved by using sodium dodecyl sulfate as a dispersant. Different analytical tools were used to characterize the nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 33 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…In addition, SnO 2 NPs can roll or slide between two friction surfaces to prevent adhesive wear. CeO 2 NPs (≈90 nm) were used as additives in castor oil with four different concentrations in the range 0.1%-1.0% w/v, with sodium dodecyl sulfate as a dispersant [174]. The maximum reduction in the wear scar diameter was 37.4% at the optimum concentration of CeO 2 .…”
Section: Effect Of Surface Functionalizationmentioning
confidence: 99%
“…In addition, SnO 2 NPs can roll or slide between two friction surfaces to prevent adhesive wear. CeO 2 NPs (≈90 nm) were used as additives in castor oil with four different concentrations in the range 0.1%-1.0% w/v, with sodium dodecyl sulfate as a dispersant [174]. The maximum reduction in the wear scar diameter was 37.4% at the optimum concentration of CeO 2 .…”
Section: Effect Of Surface Functionalizationmentioning
confidence: 99%
“…Prominent among these have been the friction reduction and anti-wear properties of metals, such as Fe, Cu, and Co [12,13], and metallic oxide nanoparticles, such as CuO, ZnO, TiO 2 , SiO 2 , or Al 2 O 3 [14][15][16][17]. In addition, the anti-wear, antifriction, and load carrying properties of castor oil were significantly improved with the addition of hybrid nano oxides like CeO 2 and polytetrafluoroethylene nanoparticles [18][19][20]. Li et al demonstrated that small quantities of graphene additives could diminish friction and wear scars in steel/steel metal contacts [21].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that CeO 2 nanoparticles, as an EP agent of lubricating oil, showed excellent friction-reducing performance at a very low concentration (0.01wt%), but did not improve the bearing capacity [16,17]. It was attributed to the polishing effect of CeO 2 nanoparticles on the surface of friction pairs.…”
Section: Introductionmentioning
confidence: 99%